Independent mobility on the journey to school: A joint cross-sectional and prospective exploration of social and physical environmental influences - Carver, Alison (J Transp Health, 2014)
BACKGROUND: Despite related physical/mental health benefits, children′s independent mobility for school travel (i.e. walking/cycling without adult accompaniment) has declined in recent decades. PURPOSE: To examine cross-sectional and longitudinal associations between social/physical environmental variables and independent mobility on the school journey. METHODS: Participants were 1121 9–10 year-olds residing within 1600 m of their school in urban/rural areas of Norfolk, UK in 2007 (T1). At one year (T2) 491 children were followed-up. At T1, parents survey-reported perceptions of the social/physical environment and rules regarding their child′s physical activity. Characteristics of the neighborhood, route to school and school environment were measured using a Geographical Information System and school audits. At both time-points children survey-reported their usual travel mode and whether accompanied. Regression analyses were conducted in 2013. RESULTS: Around half walked/cycled to school without adult accompaniment (T1, 43%; T2, 53%). Parents often allowing their child to play outside anywhere within the neighborhood (adjusted odds ratio (AOR) 3.14 (95% CI 1.24–7.96)) and household car access (AOR 0.27 (95% CI 0.08–0.94)) were associated longitudinally with boys walking/cycling independently to school. Land use mix (AOR 1.38 (95% CI 1.06–1.79)), proportion of main roads in the neighborhood (AOR 0.67 (95% CI 0.47–0.94)) and parental encouragement for walking/cycling (AOR 0.40 (95% CI 0.20–0.80)) were associated longitudinally with girls walking/cycling independently to school. CONCLUSIONS: Interventions should develop parents′ skills to teach their children to be independently mobile and to build confidence regarding venturing out without parental accompaniment. Urban planners should consider designing neighborhoods in which residences, business/retail outlets and sports facilities are co-located to promote active transport.